STEEL-CASTING HOUSE — THE SECOND BIRTH - V. M. Gatsuro; A. O. Glushkov (Литьë и металлургия, 2006)
The history of development of the steel-casting house of Mogilev automobile plant, which has been handed over at present to RUPP «BelAZ», is shown.